Analysis of stakeholder relationships in the industry chain of industrialized building in China - Teng, Y.; Mao, C.; Liu, G.; Wang, Xiangyu (Elsevier, 2017)
The industrialized building has been increasingly advocated as a sustainable construction technology for its potential merits of a cleanly built environment, enhanced quality performance, and reduced time and labor. However, the uncertainty within the industry chain caused by the lack of understanding of stakeholder roles and relationships affected the widespread industrialization in China. Therefore, this study aims to define the roles and determine the relationships of stakeholders within the industry chain of industrialized building using stakeholder and industrial symbiosis theories. Several methods, including literature review, face-to-face interviews, and chain referral sampling me thod, were used to identify stakeholders. Stakeholder relationship was determined through a quantitative symbiosis model. The data underpinning this model were collected from various channels, including expert interviews, official websites, statistical yearbooks, and annual reports. A case study of VANKE was employed as a validation object to explore the optimized strategies toward the stakeholder symbiotic relationship and system stability. The results show that developers contributed more to the symbiosis system compared with others. However, the unbalanced development of designers, module suppliers, and surveyors, as well as the lack of public acceptance destabilized the industrialized building symbiosis system. Optimized strategies were proposed, including improving public acceptance, strengthening the design process, reforming the module suppliers' production mode, and establishing the Standardized Module System. The industrial symbiosis model serves as an effective tool for quantitatively optimizing the stakeholder relationship of the industrialized building industry, which offers valuable references for practitioners to identify the process that should be optimized and the source of system instability. Therefore, both optimum resource distribution and sustainability can be achieved.